FINANCIAL FEASIBILITY STUDY OF GREEN BUILDING INVESTMENT GRAHA CIMB NIAGA JAKARTA BUILDING WITH A LIFE CYCLE COST ANALYSIS APPROACH - Purnomo, Hardiyanto; Tenriajeng, Andi Tenrisukki (Universitas Ibn Khaldun Bogor, 2022)
Global warming and climate change are undeniable global challenges. A phenomenon that cannot be underestimated. Temperature uncertainty, environmental damage, natural disasters to diseases that may arise due to global warming can be catastrophic. Green building is here to answer these challenges. Energy consumption in buildings is quite large and has an impact. The building aspect accounts for 35% and 38% of global energy use and carbon emissions, respectively. The amount of greenhouse gases is projected to reach 42.4 billion tons by 2035. The large initial cost comparison and ignorance of the benefits of green building causes investors to be reluctant to apply the Green Building concept. There is a need for an analysis of the life cycle cost (LCC) in the Green Building investment of the CIMB Niaga Graha Building so that the benefits of the Green Building concept are known. Graha CIMB Niaga is the first existing building in Indonesia to have a Green Building predicate with a Platinum level by BCAI Singapore. LCC analysis is expressed by Net Present Value of Savings (NPV), Savings Investment Ratio (SIR), Discounted Payback Period (DPP), Adjusted Internal Rate of Return (AIRR) and Sensitivity Analysis. Environmental gains are also expressed by NPV per 1 Greenhouse Gas (GHG) savings. The results showed that the investment was profitable and feasible. The profit is shown by the NPV parameter of Rp. 8,930,649,864 > 0, SIR of 2.69 > 1, DPP of 4.4 < 20, and AIRR of 43.88% greater than MARR of 11.72%. Investment is still profitable if the rate of increase in investment is below 163.44% or a decrease in electricity savings is below 61.58%. The results of the study also show that the investment is profitable and feasible in terms of environmental impact of Rp.410.039 per 1 GHG Savings.